Student Opinions Regarding Educational Game-Based Learning Media Innovation for Character Education - Irhas, I; Asrowi, A; Djono, D (Proceedings International Conference on Education Innovation and Social Science, 2022)
This research has the aim of identifying the need for innovation in the development of fun learning media in game format. Due to the swift currents of globalization, education needs to innovate in various aspects in order to create graduates who have the competence as well as the character of love for the homeland. The method used in this research is descriptive quantitative, it takes 47 students of elementary school as a research subject, the data is collected by survey method which uses a questionnaire item as a data collection tool. The data from the distribution of the questionnaires were then processed using the percentage technique. The results showed that in terms of the implementation of learning, so far students feel bored when participating in learning activities in class (83%), meanwhile the use of media used by teachers also tends not to keep up with the times, such as student handbooks (68.1 %) still dominates in learning. Students think that innovation is needed in the form of learning media with an educational game format (76.6%). It is hoped that the results of this study can be the basis for the development of learning media that are in accordance with the needs and characteristics of students.